“When You Fail, You Feel Like a Failure” : One Student’s Experience of Academic Probation and an Academic Support Program - Arcand, Isabelle; LeBlanc, Raymond N. (Alberta Journal of Educational Research, 2012)
This in-depth, qualitative study explored the experience of academic probation. It recounts the story of Mark, an undergraduate student on academic probation who participated in an academic support program to attain good academic standing. His story is contrasted to the current literature on academic probation and is considered in light of Dewey’s (1958,1938/1997, 1934/2005) theory of experience. This paper offers an important contribution to the literature on higher education by revealing a rich, complex, and unique experience which illustrates that Mark does not correspond to the typical image of probationary students depicted in the literature. This article breaks away from an oversimplified portrayal of probationary students, offers a provisional conceptualization of academic probation, and calls for further definition of the notion of academic probation. Cette étude qualitative et détaillée a porté sur l’expérience de la probation académique. Elle évoque l’histoire de Mark, un étudiant du premier cycle en probation académique qui a participé à un programme d’appui académique en vue d’améliorer son rendement. Nous comparons son histoire à la littérature actuelle sur la probation académique et l’examinons à la lumière de la théorie de l’expérience de Dewey (1958; 1938/1997; 1934/2005). Cet article représente une contribution importante à la littérature sur l’enseignement supérieur en décrivant une expérience riche, complexe et unique qui démontre que Mark ne correspond pas à l’image type des étudiants en probation tel qu’illustrée dans la littérature. Cet article s’éloigne de la représentation exagérément simplifiée des étudiants en probation, offre une conceptualisation provisoire de la probation académique et évoque le besoin d’une nouvelle définition de la notion de la probation académique.